2006
DOI: 10.1158/1078-0432.ccr-06-0338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Aminopeptidase N in Non–Small Cell Lung Cancer

Abstract: Purpose: The aim of our study is to investigate the mechanism of metastasis, to detect novel metastasis-associated molecules, and to evaluate the molecules from the point of view of clinical application. A monoclonal antibody MH8-11, which we established, recognizes a glycoprotein that is identical to aminopeptidase N (APN/CD13). APN/CD13 degrades the extracellular matrix, while it is also involved in cell motility and improves angiogenesis. Experimental Design: We investigated the expression of APN/CD13 in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
144
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 37 publications
7
144
1
Order By: Relevance
“…48 Furthermore, the overall survival rate of patients with CD151-positive non-small-cell lung cancer is reported to be much lower than that of CD151-negative patients, suggesting that high CD151 gene expression is a marker of poor prognosis in human lung carcinomas. 27 All these data support the notion that CD151 is a positive effecter of metastasis. As CD151 is able to bind with various integrin species, especially a3b1 and a6b4 integrins, it has been suggested that CD151-integrin protein complexes may play a role in cell motility probably through modulation of the interaction between integrin and ECM such as laminin-5 24 and also activation of focal adhesion kinase.…”
Section: Promatrilysin-1 Activation Through Interaction With Cd151 T supporting
confidence: 63%
See 1 more Smart Citation
“…48 Furthermore, the overall survival rate of patients with CD151-positive non-small-cell lung cancer is reported to be much lower than that of CD151-negative patients, suggesting that high CD151 gene expression is a marker of poor prognosis in human lung carcinomas. 27 All these data support the notion that CD151 is a positive effecter of metastasis. As CD151 is able to bind with various integrin species, especially a3b1 and a6b4 integrins, it has been suggested that CD151-integrin protein complexes may play a role in cell motility probably through modulation of the interaction between integrin and ECM such as laminin-5 24 and also activation of focal adhesion kinase.…”
Section: Promatrilysin-1 Activation Through Interaction With Cd151 T supporting
confidence: 63%
“…It has also been reported that the prognosis of patients with lung carcinoma is poorer in CD151-positive patients than in CD151-negative patients. 27 However, limited information is available concerning the mechanisms of CD151-mediated metastasis or interaction of CD151 with proteins other than integrins.…”
mentioning
confidence: 99%
“…Relating our work to the clinical importance of APN, analysis of human lung carcinoma tissue revealed that stromal fibroblasts are the most numerous of the APN-positive cells, and their APN expression correlated positively with increased angiogenesis and poor prognosis; similar results were obtained in patients with pancreatic carcinoma (13,(37)(38)(39). These observations suggest that tumor cells might secrete growth factors to induce a sustained APN expression in normal lung cells, which thus provide a favorable local environment (i.e., a "niche") for metastases.…”
Section: Discussionsupporting
confidence: 62%
“…4 CD151, one of the most important of the tetraspanins, has been extensively studied, especially in connection with the progression and prognosis of malignant tumors, including breast cancer, colon cancer, prostate cancer, and HCC. [5][6][7][8] Initial evidence for the involvement of CD151 in metastasis came from a study that showed specific in vivo inhibition of metastasis in a human epidermoid carcinoma by an unknown antibody. Since then, reduction of CD151 expression in primary melanocytes by small interfering RNA (siRNA) has been shown to result in the loss of motility, whereas it has little effect on the steady-state levels of integrins.…”
mentioning
confidence: 99%